The Important Role of Business Management in the Development of Micro Enterprises Supported by BMD Malang: A SWOT - Rr. Suci Palasari; Sudarmiatin, Sudarmiatin; Wening Patmi Rahayu (Cita konsultindo, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in driving economic growth. The micro businesses fostered by BAZNAS operate in several sectors, one of which is the culinary field. BAZNAS provides special assistance to micro-entrepreneurs to implement business management so that it can be well-organized. This research aims to understand the important role of business management in the development of micro-enterprises fostered by BAZNAS. The results of this study are expected to provide deeper insights into the role of business management in the development of micro-enterprises and to offer useful recommendations for BAZNAS and other institutions with similar programs. This research is a qualitative study using Miles and Huberman's analysis. The purposive sampling method was used when selecting informants. The informants in this study are eight micro enterprises. The aspects of company management provide guidelines for conducting business management. BAZNAS's micro-business actors in the culinary field have not yet maximally implemented these aspects, due to several factors such as low human resource quality and limited capital. The use of SWOT analysis should also be considered as a strategic tool for them to compete in markets beyond their region. The government and related institutions must give greater attention to micro-entrepreneurs as part of the people's economy, especially in terms of guidance and funding sources.